PD-1 Controls Tonic Signaling and Lymphopenia-Induced Proliferation of T Lymphocytes - Ellestad, Kristofor K.; Lin, Jiaxin; Boon, Louis; Anderson, Colin C. (Frontiers in Immunology, 2017)
Recovery of the T lymphocyte compartment within a lymphopenic host by lymphopenia induced proliferation (LIP) is regulated by inter- and intraclonal competition for limited resources including homeostatic cytokines and peptide:MHC (pMHC) complexes with which the TCR can interact at least weakly to yield a tonic signal. Importantly, the process of LIP can synergize with other factors that promote T cell activation to drive inflammatory disease. While reconstitution of the lymphoid compartment of immune deficient Rag-/- mice by transfer of wild-type hematopoietic stem cells (HSC) does not generally result in an overt disease phenotype, transfer of HSC deficient in expression of the co-inhibitory molecule PD-1 results in severe systemic autoimmunity driven by newly generated T cells that emerge from the thymus into the periphery and undergo LIP. Importantly, autoimmunity does not appear to depend on a response to exogenous (i.e. gut flora-derived) antigens. PD-1 is well known to be up-regulated during T cell activation in response to cognate antigens, but it is unclear whether PD-1 has a role in controlling LIP of T cells in the absence of cognate antigen, i.e. in response to tonic pMHC. We examined whether PD-1 controls LIP of newly generated T cells by controlling the response to tonic pMHC or the homeostatic cytokine IL-7. We found that PD-1 deficient T cells have a proliferative advantage over WT T cells during LIP and this effect is MHC-II dependent and independent of IL-7Rα signaling. Furthermore, our data suggest that signals through IL-7Rα can be dispensable for LIP and may instead be of increased importance for T cell survival in conditions of high competition for limited pMHC (e.g. post-LIP, in a lymphoreplete host). We hypothesize that autoimmunity post-PD-1-/- HSC transplant is the result of an overzealous T cell response to normally tonic self-pMHC precipitated by the synergy of LIP and PD-1 deficiency. Furthermore, potentiation of TCR signals in response to normally tonic self-pMHC may contribute to the success of PD-1 blockade in cancer immunotherapy.